GENDER DAN SEKSUALITAS: SEBUAH PERSPEKTIF ISLAM ( Judul Asli: Gender And Sexuality: An Islam Perspektif Oleh Ahmad Shehu Abdulssalam) - Puspitasari, Dewi (MUWAZAH, 2010)
Abstract: This article discusses issues of gender and sexuality from the perspective of Islam, especially wasatiyyah perspective, which is a trend of moderate Muslims who consider the current situation and their relationships with others. With reference to the al-Quran and Hadith, the relationship between men and women as described in the two sources are analyzed in detail. Issues of interest include the husband-wife relationship, marriage and divorce, polygamy, and the etiquette of socialization as well as clothing for men and women.